Systematic study of drug distribution profiles of different nanocarriers in the skin layers: a more accurate and targeted delivery - Manuela Gonçalves; Kelly Cristine Zatta; Adriana Raffin Pohlmann; Silvia Stanisçuaski Guterres (Drug Analytical Research)
The aim of this work was to evaluate the skin distributions of two drugs with different logarithm of the distribution coefficient (Log D) values. Melatonin (MEL; Log D 1.74) and benzophenone-3 (BZA-3; Log D 3.88) lipid core nanocapsules (LNCs) were prepared with poly(e-caprolactone) (PCL) of different molar weights (14,000 g mol-1 and 80,000 g mol-1), capric/caprylic triglyceride, sorbitan monostearate and polysorbate 80, and nanoemulsions (NE) were similarly prepared without polymer. In vitro release experiments combined with in vitro percutaneous penetration/permeation data demonstrated that the localization of the substance in the nanoparticles (determined by Log D) is crucial for understanding their diffusion behavior. The results demonstrated that substances of moderate lipophilicity, such as MEL, are affected by the molar mass of the polymer since the use of 80,000 g mol-1 PCL in the particle composition (LNC80MEL) guaranteed a greater encapsulation efficiency (EE%) (55%). On the other hand, the percutaneous distribution profile of substances with high lipophilicity, such as BZA-3, is not influenced by the molar mass of the polymer since for all formulations containing BZA-3, the EE% was approximately 99%. However, the presence of a polymer in the nanocapsule (LNC) tends to promote greater retention of the substance at the stratum corneum level, while its absence (NE) allows penetration of the particle through the skin layers and drives a higher concentration of BZA-3 into the dermis.